2016
DOI: 10.1002/pd.4859
|View full text |Cite
|
Sign up to set email alerts
|

MCDA twins with discordant malformations: submicroscopic chromosomal anomalies detected by chromosomal microarray analysis and clinical outcomes

Abstract: Large whole chromosome abnormalities are more common between discordant twins rather than smaller CNVs in this study. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…We found aneuploidies confined to the abnormal twin in up to 9% of the cases, similar to Peng et al with 7.5% (9/119) of genotypic discordance. 20 Increased NT and CRL discordance of over 10 mm preceded the diagnosis of a structural malformations in 20% and in 33.3% of the cases with a normal karyotype, consistent with the existing literature. 21,22 As newer molecular techniques have evolved, it is highly likely that some of the seemingly normal karyotypes would likely have had an abnormal whole exome sequencing result if they were done in cases with DCA.…”
Section: Discussionsupporting
confidence: 88%
“…We found aneuploidies confined to the abnormal twin in up to 9% of the cases, similar to Peng et al with 7.5% (9/119) of genotypic discordance. 20 Increased NT and CRL discordance of over 10 mm preceded the diagnosis of a structural malformations in 20% and in 33.3% of the cases with a normal karyotype, consistent with the existing literature. 21,22 As newer molecular techniques have evolved, it is highly likely that some of the seemingly normal karyotypes would likely have had an abnormal whole exome sequencing result if they were done in cases with DCA.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, however, the incidence of discordant karyotype was higher (10.0%) in MCDA twins with structural anomaly as the single indication for prenatal diagnosis. Peng et al . reported that discrepancies in chromosomal aberrations and CNVs were identified in 9.2% (11/119) of MCDA twin pairs with discordant anomalies, including those complicated with TTTS and sIUGR.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, the incidence of discordant karyotype was higher (10.0%) in MCDA twins with structural anomaly as the single indication for prenatal diagnosis. Peng et al 22 reported that discrepancies in chromosomal aberrations and CNVs were identified in 9.2% (11/119) of MCDA twin pairs with discordant anomalies, including those complicated with TTTS and sIUGR. These findings demonstrate that amniocentesis of both sacs is necessary for MCDA pregnancies, especially those complicated by hydrops fetalis or discordant anomalies, because parents can opt for selective reduction instead of termination of the entire pregnancy when one fetus may be healthy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological mechanism involves the development of a discrepancy in placental blood flow between the two fetuses, due to the presence of placental vascular anastomoses, one being the donor and the other the recipient. The number and type of anastomoses (arterial-to-arterial, venous-to-venous, or arterial-to-venous) determine the severity of the case (5,6).…”
Section: Introductionmentioning
confidence: 99%